The impact of socioeconomic and demographic factors on individuals’ behaviour towards their health and general well-being in rural Sindh, Pakistan - Sarfaraz, Maria Binte; Shazad, Amir; Naeem, Mustafa; Barkat, Rahil; Narawish, Chutimon; Avendano Caprilesez, Camilo Andres (International Journal Of Community Medicine And Public Health, 2021)
Background: Health and general well-being might sound like a mundane concept for most developed nations; however, it is not perceived similarly in underdeveloped areas of the developing nations. In Pakistan, the concept becomes even more foreign and muddled with certain stubborn biases which needs to be accessed. Therefore, we conducted a study to identify the impact of socioeconomic and demographic factors associated with behaviors regarding health and general well-being. Methods: A cross-sectional study was conducted in rural health centers (RHCs) of five districts of Sindh, Pakistan, from October 2020 to December 2020. A survey questionnaire was designed to collect data on socio-economic and demographic factors and their impacts on behavior towards health and general well-being. Statistical analysis was performed using STATA Version 16.0. Chi-square test and logistic regression analysis were used to determine the extent of association between predictor variables and outcome variables. Results: A total of 969 respondents participated in the study. The mean age of the respondents was 35.70 (±13.17) years. Majority of the participants (82.77%) had limited access to the required health care facility and only (3.61%) of respondents reported that they regularly consult with disease specialists. Multivariable logistic regression revealed the ability to bear disease expenses (OR=0.55, p=0.009), level of education (OR=1.81, p=0.026), female gender (OR=0.30, p=0.048), access to required health facilities (OR=0.58, p=0.012) were significantly associated with positive behavior towards health and general well-being. Conclusions: The study shows that ease of access to healthcare facilities would encourage the population to seek more healthy behaviors. Resources for promoting healthy lifestyle choices in the general population should be more comprehensive for encompassing cognitive beliefs that target psychological and physical health outcomes.